Epithelial-to-mesenchymal transition (EMT) induced by inflammatory priming elicits mesenchymal stromal cell-like immune-modulatory properties in cancer cells - Ricciardi, M (Br J Cancer, 2015)
BACKGROUND: Epithelial-to-mesenchymal transition (EMT) has a central role in cancer progression and metastatic dissemination and may be induced by local inflammation. We asked whether the inflammation-induced acquisition of mesenchymal phenotype by neoplastic epithelial cells is associated with the onset of mesenchymal stromal cell-like immune-regulatory properties that may enhance tumour immune escape. METHODS: Cell lines of lung adenocarcinoma (A549), breast cancer (MCF7) and hepatocellular carcinoma (HepG2) were co-cultured with T, B and NK cells before and after EMT induction by either the supernatant of mixed-lymphocyte reactions or inflammatory cytokines. RESULTS: EMT occurrence following inflammatory priming elicited multiple immune-regulatory effects in cancer cells resulting in NK and T-cell apoptosis, inhibition of lymphocyte proliferation and stimulation of regulatory T and B cells. Indoleamine 2,3-dioxygenase, but not Fas ligand pathway, was involved at least in part in these effects, as shown by the use of specific inhibitors. CONCLUSIONS: EMT induced by inflammatory stimuli confers to cancer cells some mesenchymal stromal cell-like immune-modulatory properties, which could be a cue for cancer progression and metastatic dissemination by favouring immune escape.